2020
DOI: 10.1101/2020.08.25.20179945
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impaired Scaling of Step Length in Parkinsonian Postural Instability

Abstract: Background: Postural stepping is an important strategy for recovery of balance in response to postural perturbations. It is disrupted by Parkinson's disease (PD) and other conditions. The nature of this disruption remains poorly understood. Understanding the motor control nature of this impairment can guide the development of novel interventions. Objectives: To identify the motor control abnormalities responsible for parkinsonian impairment of postural stepping. Methods: We studied four groups of participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Prior findings have demonstrated that the ability to scale step length with pull intensity declines with age and/or disease progression and that increased step length intercept values appear to be a compensatory measure to ensure postural stability in the face of this decline. 17 Studies examining the postural step response using standardized perturbations in PD patients have generally shown that PD patients take smaller steps than healthy subjects, [20][21][22][23] with slower reaction times that may be due to an increase in the number 22 and size 21 of anticipatory postural adjustments prior to stepping. This suggests that the kinematic deficits captured within these parameters are not necessarily disease-specific.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior findings have demonstrated that the ability to scale step length with pull intensity declines with age and/or disease progression and that increased step length intercept values appear to be a compensatory measure to ensure postural stability in the face of this decline. 17 Studies examining the postural step response using standardized perturbations in PD patients have generally shown that PD patients take smaller steps than healthy subjects, [20][21][22][23] with slower reaction times that may be due to an increase in the number 22 and size 21 of anticipatory postural adjustments prior to stepping. This suggests that the kinematic deficits captured within these parameters are not necessarily disease-specific.…”
Section: Discussionmentioning
confidence: 99%
“…Plots were created using the R package "ggplot2." Supplemental Table 1 contains a description and interpretation of the relevant kinematic variables while Supplemental Figure 1 demonstrates the relevant points of interest for each individual trial 17 . Statistically significant differences in center of mass velocity (V COM ) plots were considered to be non-overlapping 95% confidence intervals of timeframes 50 ms or greater.…”
Section: Methodsmentioning
confidence: 99%